Development as modernity, modernity as development - Lushaba, Lwazi (Interventions series., 2009)
This book analyses the impact of the Western idea of 'modernity' on development and underdevelopment in Africa. It traces the genealogy of the Western idea of modernity from European Enlightenment concepts of the universal nature of human history and development, and shows how this idea was used to justify the Western exploitation and oppression of Africa. It argues that contemporary development, theory and practice is a continuation of the Enlightenment project and that Africa can only achieve real development by rejecting Western modernity and inventing its own forms of modernity. The book i.